Penegakan Hukum Larangan Mendirikan Bangunan di Daerah Milik Jalan di Kota Batam - Ibrahim Ibrahim (Journal of Law and Policy Transformation, 2017)
The state is obliged to seek public order and public at the same time is obliged to comply with any regulatorion and government decisions relating to public order. In Batam, as well as in other cities in Indonesia, public order offenses are still common, including violations of the prohibition of building in the roads. This is a socio-legal study that uses primary data which were obtained from interviews and observations. Secondary data consists of primary and secondary legal materials were obtained from library research. Batam City Government through the Civil Service Police Unit and the Integrated Team appointed by the Mayor of Batam City are law enforcers who are assigned to ban buildings in the roads area used the following lews as their references: Law No. 38 of 2004 concerning Road and its Government Regulation Implementation, the Batam City Regulation No. 16 of 2007 on Public Order, the Batam City Regional Regulation No. 6 of 2013 on the Civil Service Police Unit and the Batam City Mayor Regulation No. 32 of 2013 on the Job Description of Batam Civil Service Police Unit. The implementation of the laws encounter obstacles, namely law enforcement factors, means and legal facilities, community factors, and cultural factors. Hence, it is suggested that it is a need of policy adjustments to strengthening law enforcement, providing means and facilities,and improving legal cultural of community. === Negara berkewajiban mengupayakan ketertiban umum dan masyarakat pada waktu sama wajib mematuhi setiap pengaturan dan keputusan pemerintah berkaitan dengan ketertiban umum itu. Di Kota Batam, sebagaimana juga di kota lainnya di Indonesia, pelanggaran ketertiban umum masih sering terjadi, termasuk pelanggaran pelarangan membangun di Daerah Milik Jalan. Penelitian ini merupakan penelitian yuridis-sosiologis yang menggunakan data primer yang diperoleh dengan wawancara dan observasi. Data sekunder terdiri dari bahan hukum primer dan sekunder yang diperoleh melalui penelusuran pustaka. Pemerintah Kota Batam melalui Satuan Polisi Pamong Praja dan Tim Terpadu yang diangkat oleh Walikota Batam di dalam melaksanakan penegakan hukum larangan mendirikan bangunan di Daerah Milik Jalan berpedoman pada dan menurut cara yang diatur dalam Undang-Undang Nomor 38 Tahun 2004 tentang Jalan dan Peraturan Pemerintah pelaksanannya, Peraturan Daerah Kota Batam Nomor 16 Tahun 2007 Tentang Ketertiban Umum, Peraturan Daerah Kota Batam Nomor 6 Tahun 2013 Tentang Satuan Polisi Pamong Praja Kota Batam dan Peraturan Walikota Nomor 32 Tahun 2013 Tentang Uraian Tugas Satuan Polisi Pamong Praja Kota Batam. Penegakan hukum larangan ini dalam penerapannya ternyata menghadapi kendala dari faktor penegak hukum, faktor sarana dan fasilitas hukum, faktor masyarakat,dan faktor budaya sehingga dibutuhkan penyesuaian kebijakan, penguatan sarana dan fasilitas penegakan hukum, perbaikan budaya hukum masyarakat.